2010
DOI: 10.1021/es101565j
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Characterization of Silver Sulfide Nanoparticles in Final Sewage Sludge Products

Abstract: Nanosized silver sulfide (α-Ag(2)S) particles were identified in the final stage sewage sludge materials of a full-scale municipal wastewater treatment plant using analytical high-resolution transmission electron microscopy. The Ag(2)S nanocrystals are in the size range of 5-20 nm with ellipsoidal shape, and they form very small, loosely packed aggregates. Some of the Ag(2)S nanoparticles (NPs) have excess S on the surface of the sulfide minerals under S-rich environments, resulting in a ratio of Ag to S close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
347
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 523 publications
(376 citation statements)
references
References 34 publications
21
347
0
6
Order By: Relevance
“…Nanoparticles are unlikely to enter the soil in their original form, however, because of the organically rich and reactive environments of WWTPs [30]. Silver sulfide NPs, found in sewage sludge, are suggested to have been formed from the reaction of Ag NPs with sulfide in a reductive environment [31].…”
Section: Sources Of Metal-based Nps In Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticles are unlikely to enter the soil in their original form, however, because of the organically rich and reactive environments of WWTPs [30]. Silver sulfide NPs, found in sewage sludge, are suggested to have been formed from the reaction of Ag NPs with sulfide in a reductive environment [31].…”
Section: Sources Of Metal-based Nps In Soilmentioning
confidence: 99%
“…Chem. 31,2012over nine months, with concomitant formation of a number of Zn precipitates [53]. However, the number of studies on NP dissolution in soil remains very small because of the technically challenging nature of such work.…”
Section: Dissolutionmentioning
confidence: 99%
“…Inorganic sulfide in wastewater effluent and receiving water has been shown to be present at concentrations that are 200 to 300 times in excess of the total Ag [87]. Silver sulfide has been identified recently in the form of nanoparticles (5-20 nm ellipsoids) in final stage sewage sludge materials in a full-sized municipal wastewater treatment plant [88]. Kim et al suggested, based on the results of Choi et al [86], that the source of the silver sulfide nanoparticles may have been engineered AgNPs.…”
Section: Case Study Iv: Monitoring For Agnps In Sewage Sludgementioning
confidence: 99%
“…This conclusion is corroborated by a study that identified Ag 2 S nanoparticles in the effluent of fullscale WWTPs. 76 In marine environments, chloride may be the principal ligand influencing AgNP dissolution.…”
Section: Effects Of Ligands and Surface Coating On Agnp Dissolutionmentioning
confidence: 99%